Manganese Exposure Aggravates β-Amyloid Pathology by Microglial Activation - Lin, Geng; Li, Xinlu; Cheng, Xiaofeng; Zhao, Ning; Zheng, Wei (Frontiers in Aging Neuroscience, 2020)
Human epidemiological evidence and animal experimental data suggest that chronic manganese (Mn) exposure increases the risk of Alzheimer’s disease (AD) and amyloid plaques, a hallmark of AD brain pathology, but the underlying mechanisms were not fully understood. Using the transgenic APP/PS1/Tau triple transgenic AD (3×Tg-AD) mouse model and mouse-derived microglia and neuroblastoma cell lines, we found that chronic 5-month Mn treatment increased beta amyloid peptide (Aβ) expression and Aβ plaques in the cerebral cortex and hippocampus in these 3×Tg-AD mice. Furthermore, we found that the β- and γ-secretase cleavage activities were markedly increased, while α-secretase cleavage activity was reduced in the brain of Mn-treated AD mice; these effects increase Aβ production and thus are amyloidogenic. Equally important, Mn treatment alone did not alter β-secretase 1 (BACE1) gene expression or Aβ production in amyloidogenic mutant amyloid precursor protein (APP) gene hAPPsw-transfected N2a cells (APPsw-N2a), but in APPsw-N2a cells either co-cultured with microglia or cultured with microglia-conditioned media, Mn exposure increased BACE1 expression and amyloidogenesis. We further determined that Mn exposure promoted the activation of microglia both in 3×Tg-AD mouse brains and in cultured microglia cells, and increased the secretion of the inflammatory cytokines interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α). Taken together, these results suggest that Mn may increase the release of IL-1β and TNF-α from microglia that in turn stimulates the expression of BACE1 gene and protein and consequently Aβ production; this novel molecular mechanism not only advances our understanding about the amyloidogenic effect of chronic Mn exposure reported for special human populations but also indicates Mn dyshomeostasis as a potential contributor to AD pathogenesis.